Kepemimpinan Perempuan dalam Perspektif Islam di Era Modern - Hazani, Dewi Chandra (Lembaga Yasin AlSys, 2022)
Woman in the modern era has been undergoing a significant role in public context in which they are not confined to the domestic sphere anymore. In fact, many of them have become leaders in communities, certain organizations even a president of a nation. Nevertheless, women are still often positioned as the second creature. This fact seems still to occur in religiousness context. For instance, in Islamic leadership, they are considered not to be placed in the top position or leader. Women are still considered that they do not have male’s character such as braveness and strangeness as the required potencies to be a leader. This paper will try to analyze the issue of woman leadership by using religion sociology analysis. Based on the result of the research, it was found that Islam religion provides wide opportunity for women to take part in a variety of ways